ENHANCING STUDENTS PROBLEM SOLVING CAPABILITY WITH ELECTRONIC STUDENT WORKSHEET BASED ON PROBLEM BASED LEARNING - Putu Victoria Maria Risamasu; Jan Pieter (PEDAGOGIK : JURNAL PENDIDIKAN, 2024)
This research was motivated by the unavailability of learning media in the form of electronic student worksheet for physics learning in schools, this type of research was r & d research. The aim of this research ware to determine the validity of electronic student worksheet, the impact of its use on problem solving abilities and the practicality of the electronic student worksheet being developed. The research population and sample were high school level students in Jayapura city. The instruments used were validity questionnaires and practicality questionnaires that were developed. Data analysis was carried out using quantitative data analysis. the results of data processing show that the electronic student worksheet based on problem based learning that was developed is suitable for use in physics learning, expert validators provide validation results of 92,64% (very good category), while the average validation results by practitioners is 96.60% (very good category); the percentage increase in n-gain in the problem solving ability of the experimental group that used electronic student worksheet was 0.73 in the high category, while the control group that used conventional lkpd was 0.46 in medium category. it was found that average practicality test result for using electronic student worksheet was 94.87%, classified as very practical.